2011
DOI: 10.1002/pd.2697
|View full text |Cite
|
Sign up to set email alerts
|

Placental volume and three‐dimensional power Doppler analysis in prediction of pre‐eclampsia and small for gestational age between Week 11 and 13 weeks and 6 days of gestation

Abstract: Objective To assess three-dimensional placental volume measurement and three-dimensional power Doppler (3D-PD) indices between 10 weeks and 6 days and 13 weeks and 6 days in predicting pregnancy-induced hypertension (PIH) and small for gestational age (SGA).Methods Three hundred and eight women undergoing fetal nuchal translucency measurement were prospectively assessed using three-dimensional ultrasound in order to measure placental volume and 3D-PD indices: vascularization index (VI), flow index (FI) and vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 26 publications
9
43
2
2
Order By: Relevance
“…This technology may allow a more direct evaluation of the abnormal placentation process thought to herald the development of preeclampsia. In agreement with the observations of other authors [4-8], we have shown that women with preeclampsia have significantly lower placental volume and vascularization indices at first trimester [9]. However, the use of 3D ultrasound parameters as risk factors for preeclampsia has been little studied, with discrepancies in the results published to date.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…This technology may allow a more direct evaluation of the abnormal placentation process thought to herald the development of preeclampsia. In agreement with the observations of other authors [4-8], we have shown that women with preeclampsia have significantly lower placental volume and vascularization indices at first trimester [9]. However, the use of 3D ultrasound parameters as risk factors for preeclampsia has been little studied, with discrepancies in the results published to date.…”
Section: Introductionsupporting
confidence: 69%
“…Dar et al [6] suggested that measurement of vascularization index, flow index, and vascularization flow index in early pregnancy may provide an effective first-trimester screening method for preeclampsia, but their series was small. Odibo et al [7] and Odeh et al [8] indicated that placental volume vascular indices as independent risk factors for preeclampsia had limited value, but no distinction was made between early and late preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Dengan kemajuan terbaru dalam 3D USG daya Doppler, evaluasi yang lebih kuat dari vaskularisasi dan aliran darah plasenta dapat dilakukan. 25 Penelitian yang dilakukan Odeh 26 menyatakan, 3D Power Doppler dari plasenta pada trimester pertama bisa memprediksi masalah pada kehamilan tetapi tidak dapat mendeteksi perbedaan indeks aliran darah pada wanita yang mengalami PE dan volume plasenta tidak sesuai untuk memprediksi PE pada tahap awal. Blood Pressure and Mean Arterial Pressure (MAP) Perubahan kecil dalam tekanan darah adalah penanda risiko berkembangnya PE.…”
Section: -24unclassified
“…Une corrélation positive était confirmée entre les indices 3D et la sévérité de RCIU [45]. Au 1 er trimestre, tous les paramètres vasculaires du placenta mesurés par Doppler 3D en cas de RCIU restaient similaires avec ceux mesurés chez les témoins [39,40,46]. Une étude concernant une population ayant une concentration de protéine plasmatique placentaire de type A (PAPP-A) basse [47] retrouvait un volume placentaire significativement diminué dans cette population par rapport aux valeurs de références.…”
Section: Retard De Croissance Intra-utérinunclassified